2014
DOI: 10.5588/pha.14.0073
|View full text |Cite
|
Sign up to set email alerts
|

Retention in pre-antiretroviral treatment care in a district of Karnataka, India: how well are we doing?

Abstract: About four in 10 individuals in pre-ART care were lost to follow-up within 1 year of registration. This needs urgent attention. Routine cohort analysis in the national programme should include those in pre-ART care to enable improved review, monitoring and supervision. Further qualitative research to ascertain reasons for loss to follow-up is required to design future interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…33 Delay in initiation of cART after diagnosis is known to be associated with patients being lost to follow-up with delayed presentation for treatment at a later date. 33,34 We analyzed patient data at the initiation of cART and not at entry into HIV care at diagnosis. In May 2017, NACO implemented a change in HIV treatment guideline to treat all individuals with HIV irrespective of CD4 count.…”
Section: Discussionmentioning
confidence: 99%
“…33 Delay in initiation of cART after diagnosis is known to be associated with patients being lost to follow-up with delayed presentation for treatment at a later date. 33,34 We analyzed patient data at the initiation of cART and not at entry into HIV care at diagnosis. In May 2017, NACO implemented a change in HIV treatment guideline to treat all individuals with HIV irrespective of CD4 count.…”
Section: Discussionmentioning
confidence: 99%
“…12 In a cohort of PLHIV attending a public ART center in Karnataka between 2010 and 2012, factors associated with loss to care at 12 months included age greater than 45 years, low educational level, being unmarried, rural residence, and advanced World Health Organization stage disease. 13 Improving our understanding of the factors that contribute to loss to HIV care in the current era of "Test and Treat" in India would help identify PLHIV at risk for loss to care and who would potentially benefit from interventions to keep them in care and virologically suppressed. To help fill this knowledge gap, we conducted a qualitative study at a large, private ART care center in southern India to identify the factors contributing to loss to HIV care in India.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Previously published studies from India have confirmed these findings: about 20-26% of diagnosed PLHIV are lost before being registered at the ART centres, while 40-80% of ART-ineligible PLHIV are lost after registration at ART centres during pre-ART care. [5][6][7][8][9] There is no published evidence in India as to what proportion of ART-eligible PLHIV are lost before initiating ART. Analysis of routinely reported aggregate data from the National AIDS (acquired immune-deficiency syndrome) Control Programme (NACP) in the state of Gujarat, India, indicates that the gap between the number of people eligible for ART initiation and the number actually initiated on ART was approximately 12% in 2014-2015.…”
mentioning
confidence: 99%
“…13,14 These factors tend to be context-specific, however, and there are challenges in generalising them to the national situation in India. While previous publications from India have quantitatively assessed the factors associated with pre-ART attrition among ART-ineligible PLHIV, [5][6][7][8] they have not provided insights into the reasons for attrition, which require qualitative study. 6,7 We therefore aimed to quantify, among PLHIV enrolled for care in two districts of Gujarat, the gap between being recorded as eligible for ART and initiation on ART within 2 months of eligibility, and to assess the factors (both quantitatively and qualitatively) associated with non-initiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation